The Effect of Different Doses of Alcoholic Extract of Alfalfa on the Control of Oxidative Stress by Nicotine in the Ovaries of Female Rats - Sajjad Sistani; Mahdieh Raeeszadeh; Ali Akbar Amiri (Tehran University of Medical Sciences, 2017)
Background and Aim: Due to the importance of infertility caused by oxidative stress induced by nicotine, this study was to evaluate the effect of alfalfa extract in contrast with the nicotine on ovarian tissues in rats. Materials and Methods: Twenty-four adult female rats were randomly divided into 4 groups. Control group received no treatment; nicotine (0.2 mg/kg) was injected to T1 subcutaneously; and nicotine plus hydroalcoholic extract of alfalfa was prescribed to T2 and T3 orally for 25 days at 250 and 500 mg/kg, respectively. On the last day, the animals were weighed. After euthanizing the animals, their ovaries were removed and weighed. Right ovary was used for MDA measure and left ovary was fixed and stained to count the primary, secondary, graafian, and atretic follicles and corpus luteum (CL). Results: Body weight in T1 (219 gr) decreased by 10 percent, and the average compared with that of the control group, T2 and T3 was significant. The highest ovarian weight was observed in T3 group (146.66±8.94mg). In T3, the average of primary and graafian follicles and CL was higher than that of T1, but atretic follicle was lower than that of T1 group. The MDA concentration in the control group (0.35±0.01 µmol/ml) was less than that in the other groups, but the TCA in T3 (821.18±3.25 µmol/ml) was significantly more than that in T1 group (708.85±12.44).  Conclusion: The hydroalcoholic extract of alfalfa can reduce the oxidative stress caused by nicotine on ovarian tissue and probably improve fertility status.